2016
DOI: 10.22226/2410-3535-2016-3-221-226
|View full text |Cite
|
Sign up to set email alerts
|

The reason for existence of discrete breathers in 2D and 3D Morse crystals

Abstract: It is known that crystals can support discrete breathers (DBs) -periodic in time and spatially localized vibrational modes. DB does not radiate energy, as its frequency does not lie within the spectrum of small-amplitude traveling waves (phonons). DB frequency can leave the spectrum of low-amplitude oscillations due to the nonlinearity of the interatomic potentials, as it is well known that the frequency of a nonlinear oscillator depends on the amplitude. Theoretically, it was shown that DB cannot exist in a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this paper we consider the dynamics of one of the examples of active matter -a lattice of active particles with potential interaction. There exists a large body of literature on different localized excitations in conservative lattices (see, e.g., [25][26][27][28][29][30][31][32][33][34][35]). In those works it has been found that solitons and mobile discrete breathers of different configurations can propagate in two-dimensional lattices.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we consider the dynamics of one of the examples of active matter -a lattice of active particles with potential interaction. There exists a large body of literature on different localized excitations in conservative lattices (see, e.g., [25][26][27][28][29][30][31][32][33][34][35]). In those works it has been found that solitons and mobile discrete breathers of different configurations can propagate in two-dimensional lattices.…”
Section: Introductionmentioning
confidence: 99%